Pulmonary Functions and Inflammatory Biomarkers in Post-Pulmonary Tuberculosis Sequelae - Kumar Shanmugasundaram; Anjana Talwar; Karan Madan; Geetanjali Bade (Tuberculosis and Respiratory Diseases, 2022)
Background Post-tuberculosis (TB) sequelae is a commonly encountered clinical entity, especially in high TB burden countries. This may represent chronic anatomic sequelae of previously treated TB, with frequent symptomatic presentation. This pilot study was aimed to investigate the pulmonary functions and systemic inflammatory markers in patients with post-TB sequelae (PTBS) and to compare them with post-TB without sequelae (PTBWS) participants and healthy controls. Methods A total of 30 participants were enrolled, PTBS (n=10), PTBWS (n=10), and healthy controls (n=10). Pulmonary function tests included spirometry and measurement of airway impedance by impulse oscillometry. Serum levels of matrix metalloproteinase (MMP)-1, transforming growth factor-β, and interferon-γ were estimated. Results Slow vital capacity (SVC), forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1), FEV1/FVC, and peak expiratory flow were significantly lower in PTBS as compared to controls. SVC and FEV1 were significantly less in PTBS as compared to PTBWS. Total airway impedance (Z5), total airway resistance (R5), central airway resistance (R20), area of reactance (Ax), and resonant frequency (Fres) were significantly higher and respiratory reactance at 5 and 20 Hz (X5, X20) were significantly lower in PTBS as compared to PTBWS. Spirometry parameters correlated with impulse oscillometry parameters in PTBS. Serum MMP-1 level was significantly higher in PTBS as compared to other groups. Conclusion Significant pulmonary function impairment was observed in PTBS, and raised serum MMP-1 levels compared with PTBWS and healthy controls. Follow-up pulmonary function testing is recommended after treatment of TB for early diagnosis and treatment of PTBS.